Extratos de madeiras amazônicas como preservativo natural e sua influência na cor da madeira de Hevea brasiliensis - Almeida, Antonio Thiago Soares de (2023)
The research aimed to evaluate the use of ethanol extracts from residues from the processing of Amazonian wood in the improvement of color stability and biological resistance of rubber tree wood from plantations. Thus, three trees (27 years old) were collected at the Santa Maria farm, in the interior of the municipality of Cachoeiro de Itapemirim, in the south of the state of Espírito Santo, which were transformed into samples for physical, colorimetric and impregnation tests of Amazonian wood extracts. of high natural resistance (Hymenolobium flavum, Roupala montana and Dinizia excelsa), in addition to the extract of Tectona grandis. The wood had medium density and moderately stable dimensional stability. The extracts were used at concentrations 1, 2, 4 and 8% in an inhibition test for brown (Rhodonia placenta and Neolentinus lepideus) and white (Polyporus fumosus and Trametes versicolor) rot fungi. Having selected the concentrations (2, 4, and 8%) for the impregnation of the wood. The pH (3.47 - 6.80) was obtained from the extracts, and Fourier transform infrared spectroscopy (FTIR) identified compounds containing aromatic rings and other bioactive phenolics. Color stability was carried out on natural wood, impregnated, weathered and after fungus attack. To test the effectiveness of the extracts, tests were carried out with the previously mentioned fungi and xylophagous termites (dry wood and soil). The extracts of R. montana and T. grandis, at concentrations of 4 and 8%, were more efficient in color stability and control of the development of xylophagous fungi. D. excelsa and R. montana extracts, regardless of the concentration used, were more effective in controlling termites.